FAKTOR – FAKTOR YANG MEMPENGARUHI JOB SATISFACTION AUDITOR DAN HUBUNGANNYA DENGAN PERFORMANCE DAN KEINGINAN BERPINDAH KERJA AUDITOR - Ershita Wulandarie; Herry Laksito (Diponegoro Journal of Accounting, 2013)
This study aims to examine the factors that influence auditor’s job satisfaction, the effects job satisfaction on performance and turnover intentions, and how far the performances moderate the relationship between job satisfaction and turnover intention. The unit of analysis from this study is the auditor who worked on KAP in Semarang. The number of samples is 45 auditors and the data processed using SPSS. The analysis performed included tests of validity, test reliability, test classic assumptions, multiple linear regression analysis including the f test, t test, and coefficient of determination. The results of the analysis of the study can be seen that the variable consideran leadership style, structure leadership style, time budget pressures, audit complexity, and performance have a significant effect on job satisfaction. While the variable work culture of has a negative significant on job satisfaction. If the auditors are satisfied with the work, then their turnover intentions will be low. Related to the effect of performance on the relationship between job satisfaction and turnover intention, this study find evidence that performance moderate the relationship between job satisfaction and turnover intention in accounting firms. It means the negative relationship between job satisfaction and turnover intention depends on the the level of the performance.